AB0558 RISK FACTORS FOR THE DEVELOPMENT OF BREAST CANCER IN SYSTEMIC SCLEROSIS. (2nd June 2020) - Carbonell, C.; Chamorro, A. J.; Marcos, M.; Guillén del Castillo, A.; Colunga Argüelles, D.; Rubio-Rivas, M.; Argibay, A.; Marí-Alfonso, B.; Marín Ballvé, A.; Castro, A.; Madroñero-Vuelta, A. B.; Callejas-Moraga, E. L.; et al.
Abstract : Background: Prior literature shows a global increase of cancer risk among patients with systemic sclerosis (SSc). Although breast cancer (BC) is one of the most frequent malignancies in SSc patients, the characteristics of this neoplasm among SSc patients is not well established and it is uncertain whether SSc significantly increases the risk of this cancer. Objectives: Describe the characteristics and risk factors for BC among Spanish patients with SSc. Methods: Ambispective and multicenter study of patients with a diagnosis of SSc according to ACR/EULAR criteria and/or LeRoy classification included in the Spanish Scleroderma Registry (RESCLE) from 2006 to 2018. Characteristics of patients with BC were described and incidence was compared with that of the general population. Results: Among 1930 patients with SSc, 206 (10.7%) had cancer. BC was the most frequent tumor location (47 patients of 206 with cancer [22.8%]), followed by lung cancer (29, 14.1%). The risk of BC was increased in patients with SSc compared to the general population (standardized incidence ratio [SIR] 1.31; 95% CI 1.10-1.54; P = 0.003). The comparison of patients with BC and those without cancer showed that patients with BC had older age at diagnosis of SSc (50.9 vs 45.9 years, respectively; P =0.004), were more frequently diagnosed of interstitial lung disease (ILD) (30/47 [63.8%] vs 694/1714 [40.5]; P = 0.002) and pulmonary hypertension (12/24 [50.0%] vs 262/917 [28.6%]; P = 0.037), had higher frequency of puffy hands as the first manifestation of SSc (4/45 [8.9%] vs 38/1664 [2.3 %]; P = 0.023) and had more frequently primary biliary colangitis (PBC) (7 /46 [15.2%] vs 72 /1708 [4.2%]; P = 0.004). Regarding autoimmunity profile, patients with SSc and BC had a significantly higher presence of anti-Ro (11/44 [25.0%] vs 214/1528 [14.0%]; P = 0.049) and anti-mitochondrial antibodies (7/28 [25.0%] vs 96/837 [11.5%]; P = 0.039). Multivariable regression analysis showed an independent association between the puffy hands (OR = 6.40; 95% CI 1.73-23.60; P = 0.005), diagnosis of PBC (OR = 5.70; 95% CI 2.16-15.07; P = 0.001), presence of ILD (OR = 3.29, 95% CI 1.69-6.39; P <0.001) and the presence of the anti-Ro antibody (OR 2.14; 95% CI 1.01-4.56; P = 0.048) with the presence of BC. Conclusion: BC risk was increased in patients with SSc. The development of ILD, PBC, the presence of anti Ro and puffy hands as the first clinical manifestation of SSc were identified as independent factors associated with the development of BC in our cohort. References: Colaci M et al. Breast cancer in systemic sclerosis: results of a cross-linkage of an Italian Rheumatologic Center and a population-based Cancer Registry and review of the literaure. Autoimmun Rev. 2014;13(2):132-7. Zhang JQ et al. The risk of cancer development in systemic sclerosis: a meta-analysis. Cancer Epidemiol. 2013;37(5):523-7. Disclosure of Interests: Cristina Carbonell: None declared, Antonio-J Chamorro: None declared, Miguel Marcos: None declared, Alfredo Guillén del Castillo: None declared, Dolores Colunga Argüelles Consultant of: Actelion pharmaceuticals, GSK, MSD., Manuel Rubio-Rivas: None declared, Ana Argibay: None declared, Begoña Marí-Alfonso: None declared, Adela Marín Ballvé: None declared, Antoni Castro Consultant of: Actelion pharmaceuticals, GSK, MSD., Ana Belén Madroñero-Vuelta: None declared, Eduardo L. Callejas-Moraga: None declared, Vicent Fonollosa-Pla Consultant of: Actelion pharmaceuticals, GSK, MSD., Carmen Pilar Simeón-Aznar Consultant of: Actelion pharmaceuticals, GSK, MSD., on behalf of RESCLE Investigators, Autoimmune Diseases Study Group (GEAS): None declared